Papel do receptor Toll-like 4 no efeito das toxinas do Clostridioides difficile em células gliais entéricas - Barbosa, Maria Lucianny Lima (2024)
Clostridioides difficile (C. difficile) is a strict anaerobic Gram-positive bacillus spore-forming bacterium that can cause a spectrum of disorders ranging from mild diarrhea to fulminant colitis and/or death. Toll-like receptors (TLRs) are a family of pattern recognition receptors that play a crucial role in the innate immune system. Previous studies have provided evidence suggesting a potential relationship between C. difficile and TLR 2, 4 and 5. This research aims to elucidate the role of TLR4 in the effect of C. difficile toxins A (TcdA) and B (TcdB) on enteric glial cells (EGCs). Male C57BL/6 mice (8 weeks old) were infected with C. difficile (VPI10463), while the control group received only the vehicle by gavage. After three days of infection, cecal samples were collected to assess TLR4 expression by immunohistochemistry. In vitro, EGCs were challenged with TcdA or TcdB, in the presence or absence of the TLR4 inhibitor (C34). TLR4 expression was evaluated by immunocytochemistry, immunofluorescence, qPCR, and Western blotting. We also assessed the immunexpression of NF-kB p65, TNF-α, IL-6, and cleaved caspase-3, as well as the binding of phosphatidylserine to annexin-V. C. difficile toxins increased TLR4 expression in mouse intestinal tissue and enteric glial cells. The TLR4 antagonist (C34) reduced NF-kB p65 translocation to the nucleus and TNF-α expression in EGCs, without affecting IL-6 gene expression. Furthermore, intervention with C34 reduced the immunexpression of cleaved caspase-3 and cell death induced by C. difficile toxins, as evidenced by decreased phosphatidylserine-annexin V binding. In summary, our results demonstrate the crucial role of TLR4 in the pathogenesis of C. difficile infection, both in vivo and in vitro, and highlight its positive regulation during toxin exposure. Additionally, our findings underscore the significant role of TLR4 in modulating the inflammatory response and cell death in EGCs in response to C. difficile toxins.